Examining the spatially varying and interactive effects of green and blue space on health outcomes in Northern Ireland using multiscale geographically weighted regression modeling. (1st March 2023) - Wang, Ruoyu; Grekousis, George; Maguire, Aideen; McKinley, Jennifer M; Garcia, Leandro; Rodgers, Sarah E; Hunter, Ruth F
Abstract: Previous studies have mainly examined the independent effects of green or blue space on health from a perspective of spatial homogeneity, which neglects their interactive or spatially varying effects. Here, we examined the spatially varying and interactive effects of green and blue space on health using open access data in Northern Ireland (NI). Aggregate health data was collected from 2017 Northern Ireland Multiple Deprivation Measure at the Super Output Area (SOA) level. Green and blue spaces were extracted from Land Cover Map data. The proportion of grassland and the proportion of woodland for each SOA were calculated as proxies for green space, while the proportion of water bodies was calculated for measuring blue space. Spatially varying effects of green and blue space were modelled using multiscale Geographic Weighted Regression (MGWR). Interaction terms between green and blue spaces were added into the MGWR models to test the interactive association of green and blue space on different health outcomes (e.g., preventable death ratio and cancer registrations). Results indicate that associations were distributed zonally, with green and blue spaces in eastern areas of NI more strongly associated with health outcomes than in western areas. Within these large regional zones, further spatially varying effects of different green and blue spaces were observed. Grassland was generally positively associated with some health outcomes (e.g., less preventable death ratio, cancer registrations ratio, multiple prescriptions ratio, and long-term health problem or disability ratio), while the results of woodland and water body were mixed. Water bodies were found to strengthen the effect of woodland and grassland. The above results indicate that green and blue space have independently and interactive spatially varying associations with different health outcomes in NI. It is also important to combine both green and blue space elements to enhance health impacts in future interventions.